Peningkatan Keterampilan Desain Konten Media Sosial Untuk Kelompok Usia Kerja - Megi Primagara (Jurnal Pengabdian Kepada Masyarakat Kalam, 2022)
The number of industries that use websites and social media for media information, sales, and interaction with their customers give rise to new job skills, namely, the industry requires human resources who have the ability to produce social media content, one of which is graphic design skills. Currently, there is quite a lot of graphic design software available, including Microsoft PowerPoint. PowerPoint can be used to design with the consideration that its use is easier than other software, and is a common software that has been installed on every computer. Therefore, this Community Service to train youth on social media content design using PowerPoint aims to develop youth skills in design skills. So those teenagers have the provision to win competence in the industrial world later.